Stability of Golden redfish (Sebastes marinus) during frozen storage as affected by raw material freshness and season of capture. Issue 4 (16th April 2018) - Dang, Huong Thi Thu; Gudjonsdóttir, María; Karlsdóttir, Magnea G.; Van Nguyen, Minh; Tómasson, Tumi; Arason, Sigurjon
Abstract: Physicochemical changes of Icelandic golden redfish ( Sebastes marinus ) as affected by seasonal variation (June and November) and raw material freshness (processed 4 and 9 days postcatch) during frozen storage (at −25°C for 20 months) were studied to find optimal conditions for production of high‐quality frozen products. Thawing loss, cooking yield, and color of the fillets as well as chemical composition, water holding capacity, pH, total volatile basic nitrogen, lipid oxidation, and hydrolysis of the light and dark muscle were analyzed every 4 months of frozen storage. Lipid hydrolysis was the main degradation process in the light muscle, while the dark muscle was more affected by lipid oxidation. Fish caught in November showed greater instability in the analyzed parameters during storage than fish caught in June, which could be linked to differences in individual poly unsaturated fatty acids between the two seasons. The quality attributes of fish processed on day 9 were similar to fish processed 4 days postcatch, except slightly higher thawing loss and yellowness, were observed in fish processed 9 days postcatch. Stability of golden redfish through frozen storage was higher in the fish caught in June than in November. Abstract : Season of capture affected both the nutritional value and stability of golden redfish. Fish processed and frozen 9 days postcatch had slightly higher thawing loss and yellowness values compared to fish processed on day 4, but no differences were found in other quality attributes. Removing the dark muscle by deep skinning could thus improve the quality and stability of redfish fillets.